Edukasi Preventif Anti-Bullying Bagi Siswa Untuk Mewujudkan Sekolah Aman - Khairuddin; Ratna Juita; Rani Marja Safitri; Annisa Risqia Hendryani; Daffa Syiva'an Noval (CV. ITTC INDONESIA, 2026)
Bullying in elementary school environments remains a serious concern due to its long-term impact on students’ psychological and social development. This article describes the implementation of preventive anti-bullying education for fourth-grade students at SD Negeri 09 Sijunjung as part of the KKN (Community Service) program. The method employed was educational outreach through material presentation, interactive discussion, and question-and-answer sessions. The results showed that students gained understanding of the definition of bullying, its forms (verbal, social, and physical), its negative impacts, and practical prevention strategies. The education also encouraged students to be more courageous in rejecting bullying behavior and supporting a positive school environment. Psychological impacts observed in previous studies, including anxiety, low self-esteem, and social isolation, reinforce the urgency of early preventive intervention. This activity also underlines the importance of collaborative approaches involving schools, families, and external facilitators in building a safe and child-friendly school environment.